2015
DOI: 10.1097/mpa.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Stone Density on Noncontrast Computed Tomography in Predicting the Outcome of Extracorporeal Shock Wave Lithotripsy for Patients With Pancreatic Stones

Abstract: The measurement of pancreatic stone density before therapy can help predict therapeutic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
2
33
1
1
Order By: Relevance
“…If these calculi could be identified prior to subjecting them to ESWL then an alternative procedure can be advised. In a recent study Ohyama et al 42. have shown that calculi with density of >820.5 Hounsfield units on noncontrast computed tomography were associated with reduced stone fragmentation and clearance.…”
Section: Modalities Of Treatmentmentioning
confidence: 98%
“…If these calculi could be identified prior to subjecting them to ESWL then an alternative procedure can be advised. In a recent study Ohyama et al 42. have shown that calculi with density of >820.5 Hounsfield units on noncontrast computed tomography were associated with reduced stone fragmentation and clearance.…”
Section: Modalities Of Treatmentmentioning
confidence: 98%
“…The 3-point Likert-Scale was used in three studies to define pain intensity [14,19,20]. The 4-grade Pain-Scale was used in two studies as a measure of pain intensity [21,22]. One of the authors [23] used the 5-point Likert-Scale to define pain intensity.…”
Section: Pain Reliefmentioning
confidence: 99%
“…anesthesia is needed and, particularly with more than one stone in different parts of the MPD, multiple sessions are required to facilitate effective fragmentation and MPD clearance. In addition, calculi with a density of >820.5 Hounsfield units seem to respond less effectively to ESWL . As standard of practice, different interventions are needed for MPD clearance (ERCP, ESWL), which leads to additional procedures and costs.…”
Section: Introductionmentioning
confidence: 99%